Recurrent Clostridioides difficile infection worsens anxiety-related patient-reported quality of life - Richard L. Hengel; Claudia P. Schroeder; Jinhee Jo; Timothy E. Ritter; Ramesh V. Nathan; Anne J. Gonzales-Luna; Engels N. Obi; Ryan J. Dillon; Lucinda J. Van Anglen; Kevin W. Garey (SpringerOpen, 2022)
Abstract Background Clostridioides difficile infection (CDI) is associated with high recurrence rates impacting health-related quality of life (HrQOL). However, patient-reported data are lacking particularly in the outpatient setting. We assessed changes in HrQOL over time in patients treated with bezlotoxumab at US infusion centers and determined clinical factors associated with HrQOL changes. Methods The HrQOL survey was conducted in adult patients with CDI, who received bezlotoxumab in 25 US outpatient infusion centers. The survey was adapted from the Cdiff32 instrument to assess anxiety-related changes to HrQOL and completed on the day of infusion (baseline) and at 90 days post bezlotoxumab (follow-up). Demographics, disease history, CDI risk factors, and recurrence of CDI (rCDI) at 90-day follow-up were collected. Changes in HrQOL scores were calculated and outcomes assessed using a multivariable linear regression model with P < 0.05 defined as statistically significant. Results A total of 144 patients (mean age: 68 ± 15 years, 63% female, median Charlson index: 4, 15.9% rCDI) were included. The overall mean baseline and follow-up HrQOL scores were 26.4 ± 11.5 and 56.4 ± 25.0, respectively. At follow-up, this score was significantly higher for patients who had primary CDI (34.5 ± 21.7) compared to those with multiple rCDI (24.7 ± 21.0; P = 0.039). The mean HrQOL change at follow-up was significantly higher for patients without rCDI (34.1 ± 28.8 increase) compared to patients with rCDI (6.7 ± 19.5 increase; P < 0.001), indicating improvement in anxiety. Conclusions Using the Cdiff32 instrument, we demonstrated that HrQOL worsened significantly in patients with further rCDI. These findings support the use of Cdiff32 in assessing CDI-related humanistic outcomes.